Novel Transcriptional Regulatory Signals in the Adeno-Associated Virus Terminal Repeat A/D Junction Element - Haberman, Rebecca P. (American Society for Microbiology, 2000)
Adeno-associated virus (AAV) type 2 vectors transfer stable, long-term gene expression to diverse cell types in vivo. Many gene therapy applications require the control of long-term transgene expression, and AAV vectors, similar to other gene transfer systems, are being evaluated for delivery of regulated gene expression cassettes. Previously, we (R. P. Haberman, T. J. McCown, and R. J. Samulski, Gene Ther. 5:1604–1611, 1998) demonstrated the use of the tetracycline-responsive system for long-term regulated expression in rat brains. In that study, we also observed residual expression in the “off” state both in vitro and in vivo, suggesting that the human cytomegalovirus (CMV) major immediate-early minimal promoter or other cis-acting elements (AAV terminal repeats [TR]) were contributing to this activity. In the present study, we identify that the AAV TR, minus the tetracycline-responsive minimal CMV promoter, will initiate mRNA expression from vector templates. Using deletion analysis and specific PCR-derived TR reporter gene templates, we mapped this activity to a 37-nucleotide stretch in the A/D elements of the TR. Although the mRNA derived from the TR is generated from a non-TATA box element, the use of mutant templates failed to identify function of canonical initiator sequences as previously described. Finally, we demonstrated the presence of green fluorescent protein expression both in vitro and in vivo in brain by using recombinant virus carrying only the TR element. Since the AAV terminal repeat is a necessary component of all recombinant AAV vectors, this TR transcriptional activity may interfere with all regulated expression cassettes and may be a problem in the development of novel TR split gene vectors currently being considered for genes too large to be packaged.